2001
DOI: 10.1046/j.1365-3024.2001.00404.x
|View full text |Cite
|
Sign up to set email alerts
|

Antibody‐dependent cell‐mediated cytotoxicity to newly excysted juvenile Fasciola hepatica in vitro is mediated by reactive nitrogen intermediates

Abstract: Passive intraperitoneal transfer of sera from Fasciola hepatica-infected sheep, cattle or rats can protect naive rats from F. hepatica infection, suggesting a parasite killing mechanism within the peritoneal cavity that is dependent on the presence of parasite-specific antibody. We investigated antibody-dependent cell-mediated cytotoxicity by resident peritoneal lavage cell populations, containing large numbers of monocytes/macrophages, as a potential host resistance mechanism by which juvenile flukes could be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
50
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 37 publications
7
50
0
1
Order By: Relevance
“…Most importantly, these antibodies were capable of mediated killing of NEJ in conjunction with mouse peritoneal lavage adherent cells, or sheep complement in ADCC and antibody-dependent complement mediated cytotoxicity assays, respectively. Our findings are in agreement with Piedrafita et al 22 who have shown that up to 80% of F. hepatica NEJ are killed when incubated for 48-72 hr in the presence of sheep infection serum and rat peritoneal adherent cells. More importantly, FasAc14p-mediated generation of significant NEJ killing may be considered an in vitro correlate of protection, since cytotoxicity against NEJ was recently implicated as a major mechanism of Indonesian thin-tail sheep resistance against F. gigantica infection.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Most importantly, these antibodies were capable of mediated killing of NEJ in conjunction with mouse peritoneal lavage adherent cells, or sheep complement in ADCC and antibody-dependent complement mediated cytotoxicity assays, respectively. Our findings are in agreement with Piedrafita et al 22 who have shown that up to 80% of F. hepatica NEJ are killed when incubated for 48-72 hr in the presence of sheep infection serum and rat peritoneal adherent cells. More importantly, FasAc14p-mediated generation of significant NEJ killing may be considered an in vitro correlate of protection, since cytotoxicity against NEJ was recently implicated as a major mechanism of Indonesian thin-tail sheep resistance against F. gigantica infection.…”
Section: Discussionsupporting
confidence: 93%
“…About 1 ml blood were obtained from each sheep 7 days after the last injection, to evaluate serum antibody responses of individual sheep to newly excysted juvenile worms (NEJ) by indirect membrane immunofluorescence (IF), antibody-dependent cell-mediated (ADCC) and antibody-dependent complement-mediated cytotoxicity assays using standard procedures, as described. [21][22][23] Briefly, metacercariae were used 5-10 days after release from laboratory-infected snails and encystment, and the outer cyst removed by shaking for 90 min at 378C in 2% (w/v) pepsin in 0.2% HCl. Following centrifugation, the metacercariae were incubated, with shaking, for 120 min at 378C, in the presence of 0.45% taurocholic acid (ICN Biomedicals, Costa Mesa, CA) to achieve final release of outer cyst, and in the presence of high CO 2, and low O 2 tension, which was achieved by addition of 0.3% L-cysteine (anti-oxidant).…”
Section: Peptide Immunogenicity In Sheepmentioning
confidence: 99%
“…In our case, however, SOD in the culture medium did not affect the action of peritoneal cells against F. hepatica juveniles (data not shown). This result confirms what was observed by Piedrafita et al [25].…”
Section: Discussionsupporting
confidence: 93%
“…A previous study established that PC of four-week infected rats does not affect the survival of juvenile flukes cultured for 24 h and subsequently transferred to the peritoneal cavity of normal rats [8]. Conversely, Piedrafita et al showed in a recent publication that naive rat PC are able to kill NEJ in vitro when cultured in the presence of immune serum of either rat or sheep origin, and that the cytotoxic mechanism largely involves NO production [25]. The discrepancies between these results and ours could be the consequence of different experimental procedures: the effector/Target (E/T) ratio in Piedrafita's study was 1 NEJ/2 × 10 5 PC, while the E/T ratio in the present study was 6-20 times lower (3 to 10 NEJ/10 5 PC).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation